Chicken soup for the soul-- : stories for a better world - Canfield, Jack; Carter, Candice C.; Hansen, Mark Victor (Health Communications, 2005)
This celebration book returns readers to the core of the Chicken Soup mission: to tell great stories that warm the heart. touch the spirit and inspire people to be the best t